Grey blight disease of cinnamon (Cinamomum verum Bercht & Presl.) leaves - DAS, P KARUNAKARAN, M C NAIR, LULU (Journal of Spices and Aromatic Crops, 1993)
A survey on diseases affecting cinnamon (Cinnamomum verum) revealed the occurrence of grey blight of leaves caused by Pestalotiopsis palmarum in several parts of Kerala, India.